P-554 Impact of genotype and phenotype on ICSI outcomes of cystic fibrosis (CF) men patients: a cohort study about 107 ICSI from 1999 to 2019. (30th June 2022) - Chargui, A; Adjiman, L; Hubert, D; Bourdon, M; Ferreux, L; Maignien, C; Gille, A.S; Rivet Danon, D; Pocate, K; Thiounn, N; Santulli, P; Bienvenu, T; et al.
Abstract: Study question: Is there an impact of CFTR (cystic fibrosis transmembrane-conductance regulator) gene mutation type and/or general health condition of men with CF and the ICSI outcomes? Summary answer: Neither genetic severity nor clinical severity seems to have a negative impact on the biological or clinical ICSI issues for cystic fibrosis men patients. What is known already: CFTR protein regulates electrolyte and fluid transport in many tissues with exocrine function, including male reproductive tract. Mutation of CFTR gene causes CF, which affects the function of several organs, and impairs male fertility. CF is generally associated to an obstructive azoospermia because of bilateral absence of vas deferens and seminal vesicles degeneration. CFTR protein is detected in human fetus at the early developmental stages and highly expressed in testis and epididymis. CFTR provides establishment of specific fluid environment for germ cell differentiation and maturation. According to literature, it seems likely that CFTR mutations affect sperm quality and embryo development. Study design, size, duration: This cohort study was conducted in the Assisted Reproduction Center of an university hospital on 52 patients, for whom a CF has been diagnosed and monitored in the same hospital. The CF diagnosis was based on CFTR genetic tests and clinical symptoms. All men were azoospermic and underwent on a microscopic epididymal sperm aspiration (MESA) and/or a testicular sperm extraction (TESE). 52 couples underwent in total 107 ICSI with frozen sperm between 1999 and 2019. Participants/materials, setting, methods: Clinical data- one year preceding surgical sperm collection and freeze - related to the severity of the CF were collected: respiratory spirometry data, Pseudomonas aeruginosa colonization, number of antibiotic treatment, BMI and Pancreatic insufficiency, as well as CFTR mutations. Linear regression tests (fisher and χ²) were carried out to establish or not correlation between biological and clinical ICSI outcomes and on the other hand genotype and/ or each clinical parameter. Main results and the role of chance: The mean age of patients at sperm retrieval was 31.3 years [21-55]. Mean BMI was 21.3. Patients with severe genotype represented 67.8% and likely (67.3%) with external pancreatic deficiency. P.aeroginosa colonization was revealed in 30% of cases and 45.6% patients received at least one IV antibiotic treatment. Respiratory function has been impaired in 18 cases, with a maximal expiratory volume per second < 40%. Spermatozoa were found and frozen for all patients after surgical sperm retrieval (20 MESA and 32 MESA + TESE). The mean number of epididymal motile progressive spermatozoa was satisfactory (10.2±18.83 million). Women mean age was 30 years at ICSI and female infertility was associated in 15.4%. Fertilization and cleavage rates were 66% both. Mean number of transferred and/or frozen embryos per attempt was 3. Implantation rate was 20%. A total of 50 pregnancies and 44 live births were obtained (35.5% of cumulative clinical pregnancy rate per ICSI and 29.1% of live birth rate per transfer). Fertilization rate, absence of pregnancy or absence of live birth were not affected by the genetic severity (p = 0.63, p = 0.46 and p = 0.16 respectively). Likewise, and after several univariate analyses there was no statistically significant correlation between clinical severity and ICSI outcomes. Limitations, reasons for caution: Practices of assisted reproduction have constantly evolved during the study period, this concerns the controlled ovarian stimulation protocols, IVF techniques, equipment and culture media used. Our study needs to be completed by a multivariate analyse Wider implications of the findings: Regarding to better quality of life of CF patients nowadays and to our results- with no significant correlation between genetic and/or clinical severity and ICSI outcomes, surgical sperm collection can be proposed only in case of a conceptional project or before transplantation and immunosuppressive agents in order to perform ICSI. Trial registration number: for non-clinical trials